Advances in the Treatment of Pediatric Brain Tumors - Edwin S. Kulubya; Matthew J. Kercher; H. Westley Phillips; Reuben Antony; Michael S. B. Edwards (MDPI AG, 2022)
Pediatric brain tumors are the most common solid malignancies in children. Advances in the treatment of pediatric brain tumors have come in the form of imaging, biopsy, surgical techniques, and molecular profiling. This has led the way for targeted therapies and immunotherapy to be assessed in clinical trials for the most common types of pediatric brain tumors. Here we review the latest efforts and challenges in targeted molecular therapy, immunotherapy, and newer modalities such as laser interstitial thermal therapy.